Biodegradation mechanisms of p-nitrophenol and microflora dynamics in fluidized bed bioreactors - Zheng, Xin; Zhang, Yongjie; Ye, Zhiheng; Pan, Zhiyan (Frontiers in Microbiology, 2025)
p-Nitrophenol (PNP), a member of the nitroaromatic family, is widely used in the production of pesticides, dyes, pharmaceuticals, and petroleum products. As a toxic compound, PNP is highly resistance to degradation, posing a significant challenge in agricultural and industrial wastewater treatment. Conventional PNP wastewater treatment methods require complex operational conditions that incur high chemical and equipment costs, and potential secondary pollution. Therefore, this study developed an anoxic fluidized bed bioreactor (AFBBR) and an anaerobic-aerobic fluidized bed bioreactor (AAFBBR) to evaluate the biodegradation performance and underlying mechanisms of PNP over a period of 90 days. The effect of glucose to PNP co-substrate ratios and C/N ratios have been systemically investigated. At an influent PNP concentration of 100 mg/L, a glucose to PNP co-substrate ratio of 6:1, and a C/N ratio of 10:1, the degradation of PNP reached 88.8 ± 1.0% in the AFBBR at an HRT of 8.5 h and 95.3 ± 0.3% in the AAFBBR at an HRT of 12.7 h. Meanwhile, the mechanism of PNP biodegradation and microbial community were also studied. Results of the LC–MS/MS revealed the intermediate products and confirmed that PNP biodegradation in both reactors followed the hydroquinone as well as the hydroxyquinol pathways, with the hydroquinone pathway being dominant. Results of the 16S rRNA high throughput sequencing further revealed a predominant presence of Proteobacteria (34% in the AFBBR, 42 and 65% in the anaerobic as well as aerobic zones of the AAFBBR, respectively), Firmicutes (35, 40, and 4%), Saccharibacteria (14, 9, and 4%) and Bacteroidetes (5, 4, and 19%). In the AFBBR and the AAFBBR, the key bacterial genera responsible for PNP degradation include Lactococcus, Escherichia-Shigella, Saccharibacteria_norank, Acinetobacter, Comamonas, Zoogloea, and Pseudomonas. Notably, the hydroxyquinol pathway was observed only in the AFBBR and the aerobic zone of the AAFBBR, where Pseudomonas were identified as key PNP degrading bacteria. These phenomena can be attributed to the varying dissolved oxygen concentrations across different zones in the two reactors, offering valuable insights into optimizing PNP removal in pilot-scale bioreactors. This study highlights an efficient, sustainable and cost-effective approach for PNP removal from agricultural and industrial wastewater.